Linguistic skills and trust creation in international business relationships - Jauhiainen, Hanna (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Today’s international business in highly related to crossing national, cultural and linguistic borders making communication and linguistic skills a vital part of the trade. The purpose of the study is to understand the role of linguistic skills in trust creation in international business relationships. Subobjectives are to discuss the importance of linguistic skills in international business context, to evaluate the strategic value of trust in business relationships and to analyze the extent to which linguistic skills affect trust formation. The scope is restricted to business-to-business markets. The theoretical background consists of different theories and previous studies related to trust and linguistic skills. Based on the theory a new LTS-framework is created to demonstrate a process model of linguistic skills affecting trust creation in international B2B relationships. This study is qualitative using interviews as a data collection method. Altogether eleven interviews were conducted between October 2014 and February 2015. All of the interviewees worked for organizations operating in the field of international business in B2B markets, spoke multiple languages and had a lot of experience in sales and negotiations. This study confirms that linguistic skills are an important part of international business. In many organizations English is used as lingua franca. However, there are several benefits of speaking the mother tongue of the customer. It makes people feel more relaxed and it makes the relationship more intimate and allows to continue developing it at a more personal level. From the strategic point of view trust creates competitive advantage to a company adding strategic value to the business. The data also supported the view that linguistic skills definitely impact the trust formation process. Quickness and easiness could be stated as the main benefits. It was seen that trust forms faster because both parties understand each other better and they become more open about information sharing within a shorter period of time. These findings and the importance of linguistic skills in trust creation should be acknowledged by organizations, especially regarding the human resource management. Boundary spanners are in key positions so special attention should be put into hiring and educating employees which then take care of company’s relationships. Eventually, these benefits are economical and affect to the profitability of the organization

Kansainvälinen liiketoiminta on erittäin kytköksissä kansallisten, kulttuuristen ja kielellisten rajojen ylittämiseen. Tämä korostaa puolestaan kommunikaation ja kielitaidon merkitystä. Tutkimuksen tavoitteena on ymmärtää kielitaidon merkitys luottamuksen syntymiseen kansainvälisissä liikesuhteissa. Alatavoitteet ovat kielitaidon tärkeyden ymmärtäminen kansainvälisessä liiketoiminnassa, luottamuksen tuoman strategisen arvon arviointi ja kielitaidon vaikutuksen mittaaminen luottamuksen luomisessa. Tutkimus on rajattu B2B markkinoiden tarkasteluun. Teoreettinen viitekehys muodostuu eri teorioista ja aikaisemmista tutkimuksista liittyen luottamukseen ja kielitaitoon. Teorian pohjalta on luotu LTS-viitekehys havainnollistamaan kielitaidon vaikutusta luottamuksen syntymiseen kansainvälisissä B2B liikesuhteissa. Tutkimus on laadullinen ja tiedonkeruumenetelmänä on käytetty haastatteluja. Yhteensä yksitoista haastattelua tehtiin aikavälillä lokakuu 2014 ja helmikuu 2015. Kaikki haastateltavat työskentelivät kansainvälisissä yrityksissä B2B markkinoilla, puhuivat useita kieliä ja heillä oli paljon kokemusta myynnistä ja neuvotteluista. Tämä tutkimus vahvistaa, että kielitaito on tärkeä osa kansainvälistä liiketoimintaa. Vaikka monissa organisaatiossa käytetään englantia yhteiskielenä, niin asiakkaan äidinkielen puhuminen tuo monia etuja. Se rentouttaa ihmisiä ja tekee suhteesta tuttavallisemman mahdollistaen sen kehittämisen henkilökohtaisemmalla tasolla. Strategisesta näkökulmasta katsoen, luottamus tuo kilpailuetua yritykselle luoden strategista lisäarvoa. Tutkimus tukee myös näkemystä, että kielitaito todella vaikuttaa luottamuksen luomisprosessiin, varsinkin liittyen sen nopeuteen ja helppouteen. Luottamus kasvaa nopeammin koska osapuolet ymmärtävät toisiaan paremmin ja jakavat avoimemmin tietoa lyhyemmässä ajassa. Tämän tutkimuksen tulokset ja kielitaidon merkitys tulisi kiinnostaa organisaatioita, erityisesti henkilöstöjohtamisen saralla. Konkreettisen kommunikoinnin hoitavat henkilöt ovat erityisesti avainasemassa. Tämä tulisi huomioida palkatessa ja kouluttaessa työntekijöitä hoitamaan yrityksen suhdetoimintaa. Edut ovat kuitenkin lopulta taloudellisia ja vaikuttavat yrityksen kannattavuuteen